1998
DOI: 10.1002/(sici)1099-1409(199801/02)2:1<45::aid-jpp44>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Photo-oxygenation of meso-Tetraphenylporphyrin Derivatives: the Influence of the Substitution Pattern and Characterization of the Reaction Products

Abstract: The photo-oxidation reactions of several meso-tetraphenylporphyrins have been studied in order to ascertain the chemical stability of this class of compounds towards singlet oxygen. The 2,6-disubstituted ones showed an excellent stability, whilst this is not the case for other porphyrins with different substitution pattern on the phenyl rings. This parallels what has been previously found using mono-oxygenated donors. The steric effects in protecting the macrocycle seems to be predominant over the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The system Fe(III)Pc-BuOOH could operate with a one-electron mechanism-starting from the homolytic scission of the peroxo bridge O-O-when oxidizing phenols to quinones, although it oxidizes to quinones some other substrates such as anthracene and xanthene with a two-electron mechanism (as a consequence of a heterolytic scission releasing OHand affording a very reactive hypervalent intermediate), as shown by the absence of oxidative coupling products, that are typical for one-electron (radical) mechanisms. On the other hand, the significant incorporation of 18 O from 18 O 2 along the oxidation of alkynes is a convincing proof of the radical mechanism. The reasons for such varying behavior of this and other MPc catalysts is still unknown.…”
Section: Metallophthalocyanines As Redox Catalysts: An Overviewmentioning
confidence: 95%
See 1 more Smart Citation
“…The system Fe(III)Pc-BuOOH could operate with a one-electron mechanism-starting from the homolytic scission of the peroxo bridge O-O-when oxidizing phenols to quinones, although it oxidizes to quinones some other substrates such as anthracene and xanthene with a two-electron mechanism (as a consequence of a heterolytic scission releasing OHand affording a very reactive hypervalent intermediate), as shown by the absence of oxidative coupling products, that are typical for one-electron (radical) mechanisms. On the other hand, the significant incorporation of 18 O from 18 O 2 along the oxidation of alkynes is a convincing proof of the radical mechanism. The reasons for such varying behavior of this and other MPc catalysts is still unknown.…”
Section: Metallophthalocyanines As Redox Catalysts: An Overviewmentioning
confidence: 95%
“…In fact, MPcs are protected by their structure against the main threats jeopardizing redox-active metalloporphyrins, and that is the outstanding limitation towards an extensive use of the latter as industrial catalysts. First, the methinic bridges joining the pyrrole-type rings in porphyrins are the preferential targets of oxidative attack, leading initially to oxophlorins and later to macrocycle breaking and therefore to catalyst destruction [18]. Such methinic bridges are replaced in MPcs by aza bridges, which obviously are generally inert towards oxidative attacks.…”
Section: Metallophthalocyanines As Redox Catalysts: An Overviewmentioning
confidence: 99%
“…52,53 However, Silva et al demonstrated that the photooxidation reactions of several 2,6-disubstituted meso-tetraphenyl porphyrins have the chemical stability towards O 2 ( 1 Δ g ). 54 If positions 2 and 6 on the phenyl rings are blocked, the photooxidations do not take place. This excellent stability is consequence of steric effects, which protected the porphyrin ring.…”
Section: Surface Photostabilitymentioning
confidence: 99%
“…Photodegradation of the macrocycle in H 2 Por has usually been attributed to oxygen-mediated reactions that may be prompted due to absorption of photonic energy by both the porphyrin substrate and molecular oxygen. Since excited porphyrins may sensitize O 2 species to give rise to the formation of singlet molecular oxygen ( 1 D g ) along with some other radicals, it is frequently referred to as the principal reason for the photo-bleaching of porphyrins [39][40][41][42]. Hence, it is important to assess the stability range for the most promising porphyrin systems, including their protonated forms.…”
Section: Coomentioning
confidence: 99%